Knowledge, education, and information affect chronic energy deficiency among pregnant mothers in the area of Public Health Center Balen, Bojonegoro, Indonesia - Lilik Triyawati; Esti Yuliani (Universitas Airlangga, 2023)
HIGHLIGHTS One of the most common maternal health problems is the Chronic Energy Deficiency (CED) in pregnancy. Factors that lead to CED incidence were analyzed to be able to provide adequate precautions. It was found that knowledge, education, and information are factors that affect chronic energy deficiency among pregnant mothers. ABSTRACT Objective: To analyze the effect of knowledge, education and information on the incidence of chronic energy deficiency (CED) in pregnant women at Balen Health Center, Bojonegoro Regency, Indonesia. Materials and Methods: This research was a correlational analytic study with a cross-sectional approach. The sample of this study were several pregnant women at Public Health Center Balen, Bojonegoro Regency, Indonesia. There were 122 respondents who were recruited with simple random sampling. The independent variables were the predisposing factors, comprising age, number of children, education background, mother's occupational status and knowledge; the enabling factors of the prenatal class participation, and the reinforcing factors of the family support. The dependent variable was the occurrence of CED. Data collection was carried out using questionnaire and secondary data (maternal cohort). Data were processed by editing, scoring, coding, and tabulating. Data analysis used multiple logistic regression with a significance level of 0.05. Results: The most dominant factor influencing the occurrence of CED was the reinforcing factors of informative support with an Exp value (B) 3.918 and the instrument support with an Exp value (B) value of 3.450. The following factor that influenced the CED incidence was the predisposing factor of knowledge with an Exp value (B) of 2.677, the enabling factor of the prenatal class participation with an Exp value (B) of 1.793, and finally the predisposing factor of education with Exp value (B) of 0.176. Conclusion: In Balen Health Center Bojonegoro, Indonesia, the predisposing factors significantly affecting Chronic Energy Deficiency in pregnant women were knowledge and education level, while the enabling factors were availability of health facilities and prenatal class participation, and the reinforcing factors were informative support and instrument support.